Profile of an occupation – qualified tax assistant - Schambeck, Arne [Verfasser] (My University, 2026)
"The decision to pursue training in this occupation lays the foundation for a wide range of career pathways, including progression towards qualification as a tax consultant. An affinity for digital working methods is becoming increasingly important alongside an excellent understanding of numbers and attention to detail. The profile describes the key tasks, presents current training figures, and arrives at the conclusion that qualified tax assistants are often very satisfied with their training." (author's abstract; BIBB-Doku)
Keywords: S 6.4 Dienstleistungsberufe; 370; Steuerfachangestellter; Berufsbild; Tätigkeitsmerkmal; Ausbildungszufriedenheit